Implementation of Digital Marketing Strategies in MSMEs “KJ Sepatu” in Sumbersari Village Through Instagram Social Media - Anditasari, Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article discusses the implementation of digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) in Sumbersari Village, Ciparay District, Bandung Regency. The background of this research is the limited knowledge and resources of MSMEs in utilizing digital technology for marketing. The purpose of this research is to identify and implement effective digital marketing strategies to increase the competitiveness of MSMEs, especially MSMEs